Water Footprint of crop productions: A review - Lovarelli, Daniela; Bacenetti, Jacopo; Fiala, Marco (The Science of the total environment, 2016)
Water Footprint is an indicator recently developed with the goal of quantifying the virtual content of water in products and/or services. It can also be used to identify the worldwide virtual water trade. Water Footprint is composed of three parts (green, blue and grey waters) that make the assessment complete in accordance with the Water Footprint Network and with the recent ISO14046. The importance of Water Footprint is linked to the need of taking consciousness about water content in products and services and of the achievable changes in productions, diets and market trades. In this study, a literature review has been completed on Water Footprint of agricultural productions. In particular, the focus was paid on crops for the production of food and bioenergy. From the review, the development of the Water Footprint concept emerged: in early studies the main goal was to assess products' water trade on a global scale, while in the subsequent years, the goal was the rigorous quantification of the three components for specific crops and in specific geographical areas. In the most recent assessments, similarities about the methodology and the employed tools emerged. For 96 scientific articles on Water Footprint indicator of agricultural productions, this literature review reports the main results and analyses weaknesses and strengths. Seventy-eight percent of studies aimed to quantify Water Footprint, while the remaining 22% analysed methodology, uncertainty, future trends and comparisons with other footprints. It emerged that most studies that quantified Water Footprint concerned cereals (33%), among which maize and wheat were the most investigated crops. In 46% of studies all the three components were assessed, while in 18% no indication about the subdivision was given; in the remaining 37%, only blue or green and blue components were quantified. [Display omitted] •A literature review was completed on Water Footprint indicator.•An advancement development of literature was followed.•World and local studies with focus on agricultural productions were analysed.•In 61% of studies a specific geographical area was considered.•In 45% of studies grey water was assessed while in 18% only a total number was given.